Investigation of the top compression ring power loss and energy consumption for different engine conditions. (3rd April 2022) - Zavos, Anastasios; Nikolakopoulos, Pantelis G.
ABSTRACT: The engine power losses and sealing behaviour through compression rings have become a priority for engine manufactures in view of future stringent emissions standards. Historically, compression rings have great application in small road vehicles and high-performance engines. The sealing behaviour of the compression ring has a significant effect on generated friction. Therefore, the lubrication conditions in the compression ring-liner conjunction should be addressed. This study comprises ring-liner mixed hydrodynamics using a two-phase flow and a gas blow-by model. This is implemented to investigate the characteristics of a high-performance top compression ring for different engine conditions. Low, medium, and high driving speeds are examined according to world-wide harmonized light vehicles test cycle. Additionally, the impact of lubricant temperature and compression ring width on power loss and fuel consumption are investigated to display the better engine performance. GRAPHICAL ABSTRACT: UF0001